Addressing the legacy costs in an NDC reform: Conceptualization, measurement, financing - Robert Holzmann; Alain Jousten (Institute for the Study of Labor (IZA), 2010)
The paper provides a framework for the conceptualization, definition and estimation of legacy costs that need to be addressed in a reform that transforms an unfunded defined contribution (NDB) scheme into a notional (or non-financial) defined contribution (NDC) scheme. As the new contribution rate is fixed and, perhaps, reduced, paying for the accrued to date liabilities leaves a financing gap that needs to be estimated and financed, best outside the pension system if a less distorting financing form is available. The paper illustrates the proposed measurement approach with broad estimates under a hypothetical NDC reform in China.
Keywords: H55; H68; J21; J26; 330; legacy costs; pension reform; NDC; coverage expansion; Rentenreform; Gesetzliche Rentenversicherung; Umlageverfahren; Kapitaldeckungsverfahren; Rentenfinanzierung; Kosten; Theorie; Simulation; China